THE INFLUENCE OF LOVE OF MONEY, FINANCIAL LITERACY, INCOME AND DIGITAL FINANCIAL SERVICES ON PERSONAL FINANCIAL PLANNING (A Case Study of Micro and Small Enterprises in Kuningan Regency) - Munir Nur Komarudin; Ayus Ahmad Yusuf; Wildan Permana Zaenal Asikin (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2025)
The problem in this study is personal financial planning which is still a problem for some people, especially for Micro and Small Business owners in Kuningan Regency. The purpose of this study is to determine the effect of love of money , financial literacy, income and digital financial services on personal financial planning . The research method used in this study is a descriptive and verification method with a quantitative approach. The population in this study is micro and small business owners in Kuningan Regency with a total of 16,485 in 2023. In this study the author uses the Slovin formula to determine the number of samples that will be the target of the study. The data collection method uses a questionnaire or questionnaire using an interval scale of 1 to 10, and the data analysis technique used in this study is multiple linear regression analysis. The results of the study show that: (1) Love of money , Financial literacy, Income and Digital financial services together have a significant effect on Personal financial planning (2) Love of money does not have a significant effect on Personal financial planning . (3) Financial literacy does not have a significant effect on Personal financial planning . (4) Income has a positive and significant effect on personal financial planning. (5) Digital financial services have a positive and significant effect on personal financial planning.